Dune [videorecording (DVD)] - Lynch, David, 1946-; MacLachlan, Kyle, 1959-; Ferrer, José, 1912-1992; Sydow, Max von, 1929-2020-; Hunt, Linda, 1945-; Sting (Musician); Herbert, Frank (Universal Home Video, 1998)
MacLachlan is Paul Atreides, son of Duke Leto, who struggles with the native inhabitants of the dry planet Arrakis (Dune) to overthrow the terrible Baron Barkonnen and his family and control the special product of the planet, a mind-altering spice produced by giant sand worms.